4th International Symposium on Advanced Optical Manufacturing and Testing Technologies: Advanced Optical Manufacturing Technolo 2009
DOI: 10.1117/12.831002
|View full text |Cite
|
Sign up to set email alerts
|

Roughness evolution of fused silica during plasma polishing processes

Abstract: Plasma polishing process finds important applications in the fabrication of super-smooth optical surfaces. It can be applied for the precise optical surface forming and to obtain optical surfaces with ultra-low roughness and without sub-surface damage (SSD). Published results show that the plasma polishing process is mainly used for the precise optical surface forming. Very limited results are reported in literatures on the process being used for the reducing of the optical surface roughness. A novel plasma po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…With increased working pressure and radio frequency power, the etching rate and the roughness of the polished surface also increases. 60 Vana et al 61 used stainless steel X10CrNi specimen for plasma polishing and observed the change in surface roughness and gloss level of the metal surface with the time variation from 0 to 600 seconds, as shown in Figure 6. Experimentally, they found much lesser surface roughness after plasma polishing with varying gloss levels during finishing, and its value depends on the finishing time.…”
Section: Plasma Polishing Methods Applied To Various Optical Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increased working pressure and radio frequency power, the etching rate and the roughness of the polished surface also increases. 60 Vana et al 61 used stainless steel X10CrNi specimen for plasma polishing and observed the change in surface roughness and gloss level of the metal surface with the time variation from 0 to 600 seconds, as shown in Figure 6. Experimentally, they found much lesser surface roughness after plasma polishing with varying gloss levels during finishing, and its value depends on the finishing time.…”
Section: Plasma Polishing Methods Applied To Various Optical Componentsmentioning
confidence: 99%
“…A novel plasma polishing process was developed on fused silica for optical components. 69 This study utilizes capacitive-coupled hollow cathode RFexcited SF 6 and Ar plasma. The factors influencing the characteristics of the plasma were the rate of gas flow and power.…”
Section: Plasma Polishing Methods Applied To Various Optical Componentsmentioning
confidence: 99%